The Recurring Tide: Politicization and the Future of International Higher Education - Castiello-Gutiérrez, Santiago (International Higher Education, 2025)
<h3 id="the-politicization-of-international-higher-education-is-not-new-but-a-recurring-pattern-shaped-by-global-shifts-this-essay-traces-historical-debates-documented-by-international-higher-education-over-the-last-30-years-analyzing-how-past-challengesnationalism-economic-rationales-and-security-concernsmirror-todays-discussions-by-recognizing-these-cycles-we-can-explore-strategies-to-move-beyond-reactive-policies-and-foster-more-purposeful-and-sustainable-internationalization-approaches" data-pm-slice="1 1 []">The politicization of international higher education is not new, but a recurring pattern shaped by global shifts. This essay traces historical debates documented by International Higher Education over the last 30 years, analyzing how past challenges—nationalism, economic rationales, and security concerns—mirror today’s discussions. By recognizing these cycles, we can explore strategies to move beyond reactive policies and foster more purposeful and sustainable internationalization approaches.